Apologetika Terhadap Ateisme - Novrianto Renaldi lilomboba (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2021)
The Question About Existence of God from atheism, often attack the Christianity. And many of Christian do not know how to answering that. Because many Christian do not know about atheism and do not know about the danger of the atheism. The aims of this research is to know, how the Christian should answering the question about the existence of God and how the Christian responsible  their Faith to the atheism. The Method of this research is a literature analysis,  and the result of this research  can be concluded that the atheism is the result of a rational way of thinking but that rationality is not illuminated by the love of Christ and this is just like the way of every Christian who state that they are Christian or believe in God but does not show the way of life that is Obey and according with God's will.